Prevalence of Antibody to Hepatitis C Virus in Saudi Blood Donors - Bandar Al-Knawy; Awad A El-Mekki; Jamal Hamdi; Raja Thiga; Anwar Sheikha (Canadian Journal of Gastroenterology)
The prevalence of antibodies to hepatitis C virus (anti-HCV) was retrospectively determined using a second generation enzyme immunoassay in 3868 blood donors from the southern part of Saudi Arabia in an area with high prevalence of hepatitis B virus (HBV) infection. Of 3354 Saudis, 48 (1.43%) were seropositive for anti-HCV. A high prevalence (43 of 204, 21.08%) of anti-HCV was observed among Egyptian donors compared with Saudis (1.43%) and other nationalities (eight of 310, 2.58%). Furthermore, the prevalence of anti-HCV antibodies was observed to increase with age, peaking in the 25 to 34 year age group. From this and other studies conducted in different regions of Saudi Arabia, the prevalence of anti-HCV among Egyptian donors appears to range from 19.2 to 24.5%, and among Saudi donors appears to range from 1.00 to 1.7%, a rate similar to that reported from western countries; this latter rate does not seem to be influenced by the high prevalence of HBV infection in this region.